Analysis of pharmacology practices with laboratory animals: A look from the perspective of students at the Universidad Nacional de San Luis, Argentina - Teves, Mauricio Roberto; Paredes, Jésica Daniela; Giraudo, Emiliano; Paredes, María Belén; Moyano, Mario Franco; Rotelli, Alejandra Ester; Wendel, Graciela Haydée; Margarita, Alejandra Olivia; Calderón, Claudia Patricia; Lilian Eugenia (Spei Domus, 2017)
Introduction: The subject Pharmacology in the Pharmacy program is theoretical and practical, lasts a semester, and is taught in the fourth year. Practical development involves six practical laboratory sessions (tpl) and four workshops. Three tpl are for in vivo animal experiments, two for computer programs and one for in vitro techniques, allowing students to evaluate the effect of drugs through experimentation, oriented towards biological and biomedical research, and to recognize pharmacological efficacy for the treatment of diseases. Our objective was to conduct a survey to obtain a guidance instrument that allows to increase teaching quality and to know perceptions and preferences about the practices concerned. Method: A cross-sectional, descriptive study was carried out and concluded in the first four-month period of the academic year 2015. Results: 90.48% reported that animal practices were useful for training, and two-thirds considered it necessary to implement alternatives to the use of animals in their education and training. 85.71% preferred in vivo experiments, 9.52% in vitro observations and 4.76% computer programs. 90.48% responded that they would work with laboratory animals again. Conclusions: We believe that it is appropriate to work with animals in this subject; it is important to consider this practical experience in pharmacology. Students expressed their interest in knowing and interpreting the effects and mechanisms of action of drugs through in vivo observations or organs manipulated by them.